Bi2O3/rGO/MonO3n-1 all-solid-state ternary Z-scheme for visible-light driven photocatalytic degradation of bisphenol A and acetaminophen in groundwater. Issue 5 (October 2020) - Rubio-Govea, Rodrigo; Orona-Návar, Carolina; Lugo-Bueno, Sergio F.; Hernández, Netzahualpille; Mahlknecht, Jürgen; García-García, Alejandra; Ornelas-Soto, Nancy
Graphical abstract: Highlights: Bi2 O3 /rGO/MoOx Z-scheme synthesized by a mixed hydrothermal and wet-chemical route. Optimal Bi2 O3 :GO weight ratio was 300:1 in Rhodamine B degradation. Synthesized composite has good photocatalytic activity under UV and visible light. Degradation of organic pollutants in groundwater under visible light was achieved. Abstract: A series of Bi2 O3 /rGO/Mon O3n-1 all-solid-state ternary Z-scheme were successfully synthesized by a mixed hydrothermal and wet-chemical route. The new materials are highly efficient under visible-light irradiation for the degradation of rhodamine B, bisphenol A, and acetaminophen and it was shown that the best performing composite was able to degrade up to 77 % of acetaminophen in groundwater samples. The synthesized materials were characterized by Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM), X-ray Powder Diffraction (XRD), X-ray Photoelectron Spectroscopy (XPS), Nitrogen Adsorption-Desorption Isotherm and UV–vis Diffuse Reflectance spectroscopy. It was found that the presence of rGO plays an important role in the material since it helps in delaying the recombination time of photogenerated electron/hole (e − /h + ) pairs, greatly improving the photocatalytic activity of Bi2 O3 . The excellent photocatalytic activity under visible-light irradiation of Bi2 O3 /rGO/Mon O3n-1 makes it a promising material for the degradation of emerging contaminants in groundwater systems.